Antena Broadband Untuk Aplikasi TV, Seluler, dan Wifi - Muhammad Yanuar Hariyawan; Rizadi Sasmita Darwis (Politeknik Caltex Riau, 2020)
The antenna is an instrument that is important in a communication system radio.antena turn the tide terbimbing into waves free in the air and in contrast between free space with a guide can include ( coaxial cable or a / waves a waveguide ) used to meggerakkan electromagnetic energy from the source of the transmitter to or from an antenna to antenna. recipientsThe antenna have diverse forms with the dimensions and of diverse characteristics, anyway one of the antenna that attracts many research is mikrostrip. antennaThe antenna mikrostrip has several advantages of them simple forms, a compact, lightly, and cheap.On this research used antenna mikrostrip with the frequency of mhz broadband at band of frequencies 500 to 2500 Mhz.The substrate material to be used is rt duroid 5880, with dielectric constant ( εr) 2.2 and thickness ( h ) 1.57 mm. Antenna mikrostrip made using circular patches .The measurement result shows performance of returnloss antennae < -10 db at the frequency of 605 Mhz to 6677 Mhz , with bandwidth 6072 Mhz .Polaradiasi mikrostrip shaped omni directional antenna .Gain the measurement result mikrostrip antenna on the highest frequency of 650 Mhz to gain 3.3 db and at the frequency of 1800 Mhz with gain 3.4 db . The antenna received microstrip has a higher than conventional antenna which is at the frequency of Mhz 650 power accept antenna mikrostrip -33.08 dbm bigger than conventional 59.90 dbm antenna